2011
DOI: 10.1159/000329570
|View full text |Cite
|
Sign up to set email alerts
|

Fructose Malabsorption: How Much Fructose Can a Healthy Subject Tolerate?

Abstract: Background/Aims: In a prospective study, we evaluated fructose absorption capacity in 17 healthy female volunteers aged 16–27 years. Methods: All volunteers underwent analysis of their daily food intake diary and standardized breath tests. The volunteers were challenged consecutively with oral intake of 50, 25 and 15 g of fructose. Results: The average daily ingestion of fructose (19.54 ± 14.95 g) was not different between volunteers with positive and negative breath tests. On day 1, 53% of subjects exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 32 publications
1
11
0
Order By: Relevance
“… 21 , 25 , 27 , 41 47 , 50 , 51 In a series of 17 healthy controls, increasing fructose consumption from 15–25 g to 50 g resulted in increased prevalence of fructose malabsorption from 5.9% to 52.9%. 43 Another series, which compared 3 doses of fructose load (15, 25, and 50 g), also demonstrated that 100% of healthy volunteers could absorb 15 g of fructose, 90% could absorb 25 g of fructose, but only 20 to 30% could absorb 50 g. 25 Altogether these findings suggest that the physiologic dose of 25 g fructose appears to be relevant to characterize clinically significant fructose malabsorption, higher doses leading to false-positive diagnosis of fructose malabsorption. 42 …”
Section: Discussionmentioning
confidence: 97%
“… 21 , 25 , 27 , 41 47 , 50 , 51 In a series of 17 healthy controls, increasing fructose consumption from 15–25 g to 50 g resulted in increased prevalence of fructose malabsorption from 5.9% to 52.9%. 43 Another series, which compared 3 doses of fructose load (15, 25, and 50 g), also demonstrated that 100% of healthy volunteers could absorb 15 g of fructose, 90% could absorb 25 g of fructose, but only 20 to 30% could absorb 50 g. 25 Altogether these findings suggest that the physiologic dose of 25 g fructose appears to be relevant to characterize clinically significant fructose malabsorption, higher doses leading to false-positive diagnosis of fructose malabsorption. 42 …”
Section: Discussionmentioning
confidence: 97%
“…Our rationale for this time frame is that the peak of hormone release is found at about 10–15 minutes post ingestion and fructose is rapidly converted to glucose in the liver so that the time window for distinguishing fructose from glucose effects in the brain is very short [ 39 ]. More importantly, 75g of fructose is a very high load and can cause adverse events even in healthy subjects: 25g is the highest load of fructose absorbed by healthy volunteers and a fructose load of 50g induces unspecific results in 40–60% of individuals [ 43 , 44 ]. Therefore, we used 75g of glucose (as in a standard glucose tolerance test) and 25g of fructose (the highest absorbable load).…”
Section: Discussionmentioning
confidence: 99%
“…13 The second major methodological point was the limitation of the fructose intake to 25 g. Indeed, several recent studies have highlighted that 25 g was the highest amount of fructose absorbed by healthy volunteers. 14,15 According to these studies, a fructose load of 50 g induces false positive results in 40-60% of cases. 14,15 The collection of breath samples was carried out according to previous methodological recommendations in order to ensure end-alveolar breath samples.…”
Section: Discussionmentioning
confidence: 99%